IPv6 mobility support for real-time multimedia communications: A survey - Ong, Bi Lynn; Hassan, Suhaidi (2004)
Mobile Internet protocol version 6(MIPv6) route optimization improves triangular routing problem that exists in MIPv4 environment.Route optimization of Session Initiation Protocol (SIP) over MIPv6 provides efcient real-time multimedia applications to users. This article provides a survey of SIP over MIPv6. We review the processes involved during the setting up of a SIP call and during mid-call SIP mobility. When SIP transmits real-time multimedia applications in a wireless environment, the mobile node (MN) may move from one access router (AR) to another AR, handing over control from one AR to the other. High handover latency degrades the quality of real-time multimedia applications due to the fact that real-time multimedia applications are delay-sensitive.Handover latency is an important issue to discuss.Reduction of handover latency can be made possible with the use of SIP's hierarchical registration. On the other hand, hybrid hierarchical and fast handover SIP's registration performs better compared to hierarchical registration. Finally, we present the directions for future research.